LAMA PEMAKAIAN KONTRASEPSI SUNTIK BERHUBUNGAN DENGAN KEJADIAN AMENORE PADA AKSEPTOR SUNTIK - Mutia Mutia; Kamsatun Kamsatun (Poltekkes Kemenkes Jakarta III, 2017)
One of the scope of reproductive health is the mother health service that support for healthy living and able to give birth to a healthy generation and quality. The family planning program (KB) is an attempt to regulate pregnancy, the number of children, and distance of child birth to realize the quality family. Family Planning Program is also a strategy to reduce maternal mortality rate especially with 4T mother condition; too young to give birth (under 20 years of age), overeat, too close to birth spacing, and too old childbirth (over 35 years of age). The use of injectable contraception is choice of contraception most in the city of Bandung . This study aims to determine the relationship between the use of injectable contraception with the incidence of amenorrhea. The cross sectional study method. The independent variable is the duration of the use of injectable contraception, the dependent variable is the incidence amenore. The population in this study were all injecting contraception users in RW 06 Kelurahan Campaka with purposive sampling. Total sample that is 5 to 6 people. The instruments used in these two variables are interview guidelines and record medical . Analysis using Chi Square test . Results terdapat research ties between prolonged use of injectable contraceptives with the incidence of amenorrhea, with p value 0,000. As prevention of droup out on acceptor , then counseling should be done by power health take precedence and focus on replacementmethod contraception on acceptor the vulnerable there was a drop out that is acceptor the aged > 3 5 years.